2000
DOI: 10.1021/ma0008701
|View full text |Cite
|
Sign up to set email alerts
|

Plasticized Starch/Tunicin Whiskers Nanocomposites. 1. Structural Analysis

Abstract: Nanocomposite materials were obtained using glycerol plasticized starch as the matrix and a colloidal suspension of cellulose whiskers as the reinforcing phase. The cellulose whiskers, prepared from tunicin, consisted of slender parallelepiped rods with a high aspect ratio. After mixing the raw materials and gelatinization of starch, the resulting suspension was cast and evaporated under vacuum. The composites were conditioned at various moisture contents in order to evaluate the effect of this parameter on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
471
5
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 612 publications
(534 citation statements)
references
References 42 publications
37
471
5
6
Order By: Relevance
“…SO 4 ] can be due to C-O-SO 3 asymmetric stretching. The bands at 1174 cm -1 can be assigned to C-O-C from agar as in the case of cellulose dissolved in the 1-butyl-3-methylimidazolium chloride [23] and at 1168 cm -1 to ring in-plane assymetric stretching, C-C and (N)CH 2 stretching [25]. The stretching of the COH alcohol bond shifts from 1087 to 1038 cm -1 , which is probably due to the hydrogen bond formation between glycerol and macromolecule.…”
Section: Results and Discussion 31 Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…SO 4 ] can be due to C-O-SO 3 asymmetric stretching. The bands at 1174 cm -1 can be assigned to C-O-C from agar as in the case of cellulose dissolved in the 1-butyl-3-methylimidazolium chloride [23] and at 1168 cm -1 to ring in-plane assymetric stretching, C-C and (N)CH 2 stretching [25]. The stretching of the COH alcohol bond shifts from 1087 to 1038 cm -1 , which is probably due to the hydrogen bond formation between glycerol and macromolecule.…”
Section: Results and Discussion 31 Ftir Analysismentioning
confidence: 99%
“…However, no linebase changes were observed in the agar matrix used for this study. Therefore, the change of baseline in Figure 4 is probably due to the T g of glycerol-rich domains [25] or also to glycerol-water [29] or glycerol-agar associations. This last supposition/possibility can be supported by other studies on natural macromolecules gel membranes with glycerol as plasticizer [5].…”
Section: Thermal Behaviour Of Electrolytesmentioning
confidence: 98%
“…Several studies have shown that plasticizers can be used at controlled levels to adjust the degree of compliance or rigidity of films that contain nanocellulose reinforcements (Angles and Dufresne 2000;Dufresne et al 2000;López-Rubio et al 2007;Svagan et al 2007;Azeredo et al 2010;Mikkonen et al 2011;Peng et al 2011;Hansen et al 2012;Trovatti et al 2012ab;Barud et al 2013;Fortunati et al 2014;Pereda et al 2014;Alves et al 2015).…”
Section: Use Of Plasticizer Vs Mechanical Poperiesmentioning
confidence: 99%
“…The importance of glycerol as a plasticizer was shown in a study by Angles and Dufresne (2000), who prepared starch films reinforced by cellulose nano-whiskers (unusually long nanocrystals) obtained from tunicins. Without the plasticizer, the starch would have been too rigid.…”
Section: Use Of Plasticizer Vs Mechanical Poperiesmentioning
confidence: 99%
“…11,12 However, compared to conventional synthetic thermoplastics, biodegradable products based on starch, unfortunately, still exhibit many disadvantages, such as water sensitivity, poor processability, and poor mechanical properties. 13 To solve these problems, various physical or chemical modifications of the starch have been considered, including blending with other synthetic polymers, 14,15 the chemical modification, 16 or graft copolymerization, 17 and incorporating fillers such as lignin, 18 fibers or crystalline, [19][20][21][22] tunicin whiskers, 23,24 and clay. 25 Multiwalled carbon nanotubes (MWCNTs) are stiff macromolecular structures having outer diameters of about 30 nm, and lengths of 1-100 lm.…”
Section: Introductionmentioning
confidence: 99%